A chemical method for effectively removing thick oxide film from sintered Kovar alloy parts
By chemically corroding the coval alloy sintered parts under high temperature conditions using a mixed acid solution, the problem of difficult removal of the thick oxide film of the coval alloy sintered parts in the prior art is solved, and the effect of effectively removing the oxide film without damaging the glass parts is achieved.
Patent Information
- Application Number
- CN202411946910.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to effectively remove the thick oxide film of the sintered coval alloy, especially without damaging the glass parts.
The mixed acid solution is used to chemically corrode the sintered parts of the coval alloy under high temperature conditions. Through the synergistic action of hydrochloric acid and nitric acid, FeO, Fe3O4 and Fe2O3 in the oxide film are removed.
It is possible to effectively remove the oxide film on the surface of the sintered part of the Cova alloy without damaging the glass parts, and the method is simple, low-cost and good results are good.
Smart Images

Figure CN119753693A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oxide film removal, and in particular relates to a chemical method for effectively removing thick oxide films of Kovar alloy sintered parts. Background Art
[0002] Kovar alloy is an alloy with special physical and chemical properties. Its main components are iron, nickel and cobalt. The chemical composition of Kovar alloy makes it have a thermal expansion coefficient similar to that of some glass materials. In the range of 20℃~450℃, Kovar alloy has a linear expansion coefficient close to that of silicon boron hard glass, which makes it the main sealing structure material for electric vacuum devices.
[0003] Kovar alloy sintered parts are a component that combines Kovar alloy with other materials through a sintering process. Its preparation process mainly includes the following steps: first, heating the Kovar alloy and glass to a certain temperature; then, sintering them in a specific environment to make the Kovar alloy and glass composite; finally, cooling the Kovar alloy glass material to obtain the Kovar alloy sintered parts.
[0004] Kovar alloy sintered parts have a linear expansion coefficient similar to that of glass materials, which enables Kovar alloy sintered parts to be well sealed with glass. In order to ensure the reliability and stability of the seal, the connection between the Kovar alloy sintered parts and the glass will not be stressed or cracked when the temperature changes. The connection parts need to be processed to improve the sealing performance of the Kovar alloy sintered parts.
[0005] The invention patent publication document with the publication number CN116926548A discloses a preparation method of a metallographic etchant for Kovar alloy and a corrosion method thereof. The liquid phase of the metallographic etchant for Kovar alloy includes 33-35 parts of hydrochloric acid, 35-37 parts of nitric acid, 9-11 parts of sulfuric acid and 19-21 parts of water by volume, and the amount of anhydrous copper sulfate is 9-11g of anhydrous copper sulfate per 100mL of the mixed liquid; the mixed liquid phase is heated to 45°C and kept warm for 10 minutes. The corrosion method is to wipe the prepared metallographic etchant on the surface of the polished Kovar alloy metallographic sample, chemically corrode for 30-50 seconds, rinse the etchant on the sample surface with ammonia water, clean water and alcohol in turn, and after drying, observe its microstructure through an optical microscope. This patent document uses a wiping method to corrode the Kovar alloy, but the wiping effect is difficult to remove the oxide film of the Kovar alloy sintered parts. Further research is urgently needed on the corrosion process of the Kovar alloy sintered parts after sintering. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiency of the prior art that it is difficult to remove the oxide film on the surface of the Kovar alloy sintered parts by wiping corrosion, and to provide a chemical method for effectively removing the thick oxide film on the Kovar alloy sintered parts. A mixed acid solution is used. Under the synergistic effect of the two acids, the size of the glass parts will not be damaged, and the oxide film on the surface of the Kovar alloy sintered parts can be effectively removed. The method has not only simple ingredients and low cost, but also good effect of removing the oxide film by the mixed acid.
[0007] To achieve the above purpose, the technical solution provided by the present invention is:
[0008] A chemical method for effectively removing thick oxide films from sintered Kovar alloy parts, comprising:
[0009] Step 1, placing a kovar alloy and a glass through a mold in an electric furnace at a temperature above 900° C.; the electric furnace is kept warm until the glass is completely melted, the glass solidifies in the electric furnace and sintered with the surface of the kovar alloy to form an oxide film with a thickness of 200 nm to 800 nm; the kovar alloy and the glass are sintered in the electric furnace to form a kovar alloy sintered part;
[0010] Step 2, heating the mixed acid solution to 70° C. to 90° C., immersing the Kovar alloy sintered part in the mixed acid solution for 0.5 min to 2 min to ensure that the oxide film is completely removed;
[0011] Step 3, taking out the Kovar alloy sintered part of step 2, and removing the residual solution on the surface of the Kovar alloy sintered part;
[0012] Step 4: Drying to remove the moisture on the surface of the Kovar alloy sintered part with residual solution on the surface.
[0013] As a further improvement of the present invention, in the step 1, the components of the oxide film include FeO, Fe3O4, and Fe2O3;
[0014] In the step 2, the mixed acid solution removes FeO, Fe3O4, and Fe2O3 in the oxide film.
[0015] As a further improvement of the present invention, in the step 2, 1L of the mixed acid solution is prepared, and its components include: 90ml / L~110ml / L of hydrochloric acid solution, 90ml / L~110ml / L of nitric acid solution, 5g / L~8g / L of thiourea, 2g / L~5g / L of peregrine, and the balance deionized water.
[0016] As a further improvement of the present invention, the hydrochloric acid solution is prepared by mixing hydrogen chloride and water, and the specific gravity of hydrogen chloride to water in the hydrochloric acid is 1.19;
[0017] The components of the nitric acid solution include nitric acid and water, and the specific gravity of nitric acid to water is 1.42.
[0018] As a further improvement of the present invention, in step 2, the process of preparing the mixed acid solution includes:
[0019] (1) Measure 90ml~110ml of hydrochloric acid solution and pour it into a 1L beaker;
[0020] (2) Measure 90 ml to 110 ml of nitric acid solution and slowly pour it into the hydrochloric acid solution while stirring. The liquid in the beaker is a mixed acid.
[0021] (3) After the mixed acid is cooled to room temperature, deionized water is slowly added to the beaker until the liquid in the beaker is close to 1 L;
[0022] (4) Weigh 5 g to 8 g of thiourea and 2 g to 5 g of permethrin, add them to the beaker, and stir them thoroughly to melt;
[0023] (5) Slowly add deionized water to the beaker again until the liquid in the beaker is 1 L.
[0024] As a further improvement of the present invention, in the step 2, during the process of removing the oxide film, the chemical reaction equation for completely removing the oxide film by the mixed acid solution includes:
[0025] (1) The chemical reaction equations for removing FeO from the oxide film include: FeO+2HCl=FeCl2+H2O, 3FeO+10HNO3=3Fe(NO3)3+NO↑+5H2O;
[0026] (2) The chemical reaction equation for removing Fe3O4 from the oxide film includes:
[0027] Fe3O4+8HCl=2FeCl3+FeCl2+4H2O, 3Fe3O4+28HNO3=9Fe(NO3)3+NO↑+14H2O;
[0028] (3) The chemical reaction equations for removing Fe2O3 from the oxide film include: Fe2O3+6HCl=2FeCl3+3H2O, Fe2O3+6HNO3=2Fe(NO3)3+3H2O.
[0029] As a further improvement of the present invention, the step 1 comprises:
[0030] Step (11) processing the Kovar alloy into a desired shape and size, and assembling and positioning the Kovar alloy and the glass through a mold;
[0031] Step (12) The atmosphere in the electric furnace is air, and the heating temperature is 900° C. The Kovar alloy and the glass assembled in the mold are placed in the electric furnace, and the high-temperature surface of the Kovar alloy is oxidized to form an oxide film with a thickness of 200 nm to 800 nm. At the same time, the glass is melted by the heat, and the glass solidifies in the electric furnace and sintered with the surface of the Kovar alloy to form a Kovar alloy sintered part;
[0032] In step (13), the Kovar alloy sintered piece is kept warm in the electric furnace until the glass is completely melted and then cooled. The cooled Kovar alloy sintered piece is immersed in the mixed acid solution in step 2.
[0033] As a further improvement of the present invention, in the step 2, the Kovar alloy sintered piece is fixed with a hanger, and the operator wears protective gear and immerses the Kovar alloy sintered piece and the hanger into the mixed acid solution for a reaction time of 0.5 min to 2 min; specifically:
[0034] The Kovar alloy sintered piece is fixed to the hanger, and the hanger is shaken to check whether the Kovar alloy sintered piece is firmly hung, and to ensure that the hanger and the Kovar alloy sintered piece will not fall off during the pickling process;
[0035] During the preparation and pickling operations, workers must wear protective equipment to prevent the mixed acid solution from splashing and injuring workers.
[0036] As a further improvement of the present invention, in the step 2, before the Kovar alloy sintered piece is immersed in the mixed acid solution, the Kovar alloy sintered piece is first isolated and protected; specifically:
[0037] The area of the Kovar alloy sintered part that does not need pickling is isolated and protected by a plastic sleeve, an adhesive tape or a tool.
[0038] As a further improvement of the present invention, in step 3, removing the residual solution on the surface of the Kovar alloy sintered part comprises:
[0039] The Kovar alloy sintered part is rinsed with running cold water for 40 seconds to 60 seconds to remove the residual solution of the Kovar alloy sintered part;
[0040] In the step 4, the drying treatment to remove the moisture on the surface of the Kovar alloy sintered part from the residual solution on the surface comprises:
[0041] After the moisture on the surface of the Kovar alloy sintered piece is blown away by compressed air, the piece is placed in a blast drying oven and dried at 95±5° C. for 25 min to 40 min.
[0042] The advantages of the present invention are:
[0043] 1. The present invention adopts a mixed acid solution. Under the synergistic effect of two acids, the size of the glass component is not damaged, and the oxide film on the surface of the Kovar alloy sintered part can be effectively removed. It not only has simple ingredients and low cost, but also has a good effect of removing the oxide film by the mixed acid.
[0044] 2. The oxide film components of the Kovar alloy sintered part of the present invention are FeO, Fe3O4, and Fe2O3 from the inside to the outside. FeO and Fe3O4 have dense structures. FeO and Fe3O4 tightly combine the Kovar alloy and the glass, thereby achieving dense sealing of the Kovar alloy sintered part. Since the Fe2O3 structure is loose and has poor adhesion, the Kovar alloy sintered part is prone to chronic air leakage after sealing. The present invention controls the temperature of the electric furnace at above 900°C, which can control the Fe2O3 component ratio in the oxide film, improve the sintering quality of the Kovar alloy sintered part, and improve the sealing strength during sintering.
[0045] 3. The present invention uses plastic sleeves, adhesive tapes or tooling to isolate and protect the Kovar alloy sintered parts that do not require pickling, and the isolation method is simple and convenient.
[0046] 4. The present invention adopts a mixture of hydrochloric acid solution and nitric acid solution to form a mixed acid, and then assisted by common surfactants such as thiourea and pyrochlore. It can not only remove the oxide film in the unisolated protection area of the Kovar alloy sintered parts, but also will not damage the glass size. It has a large application scenario in the cleaning of the oxide film of the Kovar alloy sintered parts.
[0047] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0049] Figure 1 : A flow chart of a chemical method for effectively removing thick oxide film from Kovar alloy sintered parts provided by the present invention. DETAILED DESCRIPTION
[0050] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0051] See also Figure 1The embodiment of the present invention discloses a chemical method for effectively removing the thick oxide film of the Kovar alloy sintered parts, which uses a mixed acid solution to chemically corrode the Kovar alloy sintered parts under high temperature conditions. The mixed acid solution is prepared by using hydrochloric acid and nitric acid as pickling media, and adding additives of thiourea and pyrochlore. The embodiment of the present invention is simple to operate, low in cost, and has good effects. It can remove the oxide layer on the surface of the Kovar alloy without damaging the size of the glass parts. Specifically, the chemical method for effectively removing the thick oxide film of the Kovar alloy sintered parts disclosed in the embodiment of the present invention includes the following steps one to four:
[0052] Step 1: Put the Kovar alloy and glass through a mold in an electric furnace above 900° C.; keep the electric furnace warm until the glass is completely melted, the glass solidifies in the electric furnace and sinters with the surface of the Kovar alloy to form an oxide film with a thickness of 200nm to 800nm; sinter the Kovar alloy and the glass in the electric furnace to form a Kovar alloy sintered part.
[0053] In the above step 1 of the embodiment of the present invention, the Kovar alloy is a hard glass iron-based sealing alloy containing 29% nickel and 18% cobalt, the components of the oxide film include FeO, Fe3O4, and Fe2O3, and the Kovar alloy sintered part is a combination of the Kovar alloy and inorganic glass that are melted at high temperature and then cooled.
[0054] In practical applications, step one of the embodiment of the present invention includes: step (11) processing the Kovar alloy into the desired shape and size, and assembling and positioning the Kovar alloy and the glass through a mold; step (12) the atmosphere in the electric furnace is air, the heating temperature is 900°C, the Kovar alloy and the glass assembled in the mold are placed in the electric furnace, the high-temperature surface of the Kovar alloy is oxidized to form an oxide film with a thickness of 200nm to 800nm, and the glass is melted by heat at the same time. The glass solidifies in the electric furnace and sintered with the surface of the Kovar alloy to form a Kovar alloy sintered part; step (13) the Kovar alloy sintered part is kept warm in the electric furnace until the glass is completely melted, and then cooled, and the cooled Kovar alloy sintered part is immersed in a mixed acid solution in step two.
[0055] Step 2: Heat the mixed acid solution to 70°C to 90°C, immerse the Kovar alloy sintered parts in the mixed acid solution and react for 0.5min to 2min to ensure that the oxide film is completely removed.
[0056] In the above step 2 of the embodiment of the present invention, the mixed acid solution removes FeO, Fe3O4 and Fe2O3 in the oxide film. The embodiment of the present invention prepares 1L of mixed acid solution, and its components include: hydrochloric acid solution 90ml / L~110ml / L, nitric acid solution 90ml / L~110ml / L, thiourea 5g / L~8g / L, perchlorate 2g / L~5g / L, and deionized water as the balance. The hydrochloric acid solution of the embodiment of the present invention is made by mixing hydrogen chloride and water, and the specific gravity of hydrogen chloride to water in hydrochloric acid is 1.19; the components of the nitric acid solution include nitric acid and water, and the specific gravity of nitric acid to water is 1.42.
[0057] Further, taking the preparation of 1L solution as an example, in the above step 2 of the embodiment of the present invention, the process of preparing the mixed acid solution includes: (1) measuring 90ml~110ml of hydrochloric acid solution and pouring it into a 1L beaker; (2) measuring 90ml~110ml of nitric acid solution and slowly pouring it into the hydrochloric acid solution while stirring, and the liquid in the beaker is a mixed acid; (3) after the mixed acid is cooled to room temperature, deionized water is slowly added to the beaker until the liquid in the beaker is close to 1L; (4) weighing 5g~8g of thiourea and 2g~5g of chlorpyrifos and adding them to the beaker, stirring them thoroughly to melt; (5) slowly adding deionized water to the beaker again until the liquid in the beaker is 1L.
[0058] In the embodiment of the present invention, the mixed acid solution is heated to 70°C to 90°C by electric heating or steam heating, and then the Kovar alloy sintered piece is immersed in the mixed acid solution for reaction for 0.5min to 2min. In the embodiment of the present invention, during the pickling process, the pickling is observed while ensuring that the oxide film is completely removed, and the Kovar alloy sintered piece is taken out and rinsed with running cold water for 40s to 60s to remove the residual solution.
[0059] The thiourea in the embodiment of the present invention is thiourea, which is a common reducing substance. Thiourea can react with various oxidants to generate urea, sulfuric acid and organic compounds thereof, and can also react with organic compounds to form easily soluble addition compounds.
[0060] The pingpingjia in the embodiment of the present invention is fatty alcohol polyoxyethylene ether, which is a common non-ionic surfactant with a milky white or beige appearance and can be dissolved in various surfactants for use.
[0061] Furthermore, in step 2 of the embodiment of the present invention, in the process of removing the oxide film, the chemical reaction equation for completely removing the oxide film by the mixed acid solution includes:
[0062] (1) The chemical reaction equations for removing FeO from the oxide film include: FeO+2HCl=FeCl2+H2O, 3FeO+10HNO3=3Fe(NO3)3+NO↑+5H2O;
[0063] (2) The chemical reaction equations for removing Fe3O4 from the oxide film include: Fe3O4+8HCl=2FeCl3+FeCl2+4H2O, 3Fe3O4+28HNO3=9Fe(NO3)3+NO↑+14H2O;
[0064] (3) The chemical reaction equations for removing Fe2O3 from the oxide film include: Fe2O3+6HCl=2FeCl3+3H2O, Fe2O3+6HNO3=2Fe(NO3)3+3H2O.
[0065] In practical applications, step 2 of the embodiment of the present invention uses a hanger to fix the kovar alloy sintered parts, and the hanger is preferably nylon or plastic wire. The operator wears protective gear and immerses the kovar alloy sintered parts and the hanger in the mixed acid solution for reaction for 0.5min to 2min; specifically: the kovar alloy sintered parts are fixed on the hanger, and the hanger is shaken to check whether the kovar alloy sintered parts are firmly mounted, and ensure that the hanger and the kovar alloy sintered parts will not fall off during the pickling process; during the preparation and pickling operations, the operator wears protective gear to prevent the mixed acid solution from splashing and injuring the operator. It should be noted that during the preparation and operation of the mixed acid solution of the embodiment of the present invention, in order to avoid the harm caused by the splashing of the mixed solution, protective gear should be worn before preparing the solution or operating. Protective gear includes acid and alkali resistant clothing, rubber shoes, protective gloves and goggles.
[0066] Specifically, in step 2 of the embodiment of the present invention, the Kovar alloy sintered part is isolated and protected before being immersed in the mixed acid solution; more specifically: a plastic sleeve, tape or tooling is used to isolate and protect the area of the Kovar alloy sintered part that does not require acid washing.
[0067] Step 3: Take out the Kovar alloy sintered part from the mixed acid solution and remove the residual solution on the surface of the Kovar alloy sintered part.
[0068] In the above step three of the embodiment of the present invention, the residual solution on the surface of the Kovar alloy sintered part is removed, including: the Kovar alloy sintered part is rinsed with running cold water for 40S to 60S to remove the residual solution on the Kovar alloy sintered part.
[0069] Step 4: Drying to remove the moisture on the surface of the Kovar alloy sintered part with residual solution on the surface.
[0070] Specifically, in step 4 of the embodiment of the present invention, the moisture on the surface of the Kovar alloy sintered part with residual solution on the surface is removed by drying, including: using compressed air to blow away the moisture on the surface of the Kovar alloy sintered part, and then placing it in a blast drying oven and drying it at 95±5°C for 25min to 40min.
[0071] The embodiment of the present invention adopts a mixed acid solution of hydrochloric acid and nitric acid for pickling. Compared with the traditional single acid pickling or mechanical removal method, the mixed acid solution of the embodiment of the present invention is supplemented with common surfactants such as thiourea and pyrochlore, which can not only remove the thick oxide film on the surface of the Kovar alloy sintered parts, but also avoid damaging the glass size. Therefore, the chemical method of the embodiment of the present invention is simple, convenient, and low-cost, and has a wide application scenario in the cleaning of the oxide film of the Kovar alloy sintered parts.
[0072] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A chemical method for effectively removing thick oxide film from sintered Kovar alloy parts, characterized in that: include: Step 1, placing a kovar alloy and a glass through a mold in an electric furnace at a temperature above 900° C.; the electric furnace is kept warm until the glass is completely melted, the glass solidifies in the electric furnace and sintered with the surface of the kovar alloy to form an oxide film with a thickness of 200 nm to 800 nm; the kovar alloy and the glass are sintered in the electric furnace to form a kovar alloy sintered part; Step 2, heating the mixed acid solution to 70° C. to 90° C., immersing the Kovar alloy sintered part in the mixed acid solution for 0.5 min to 2 min to ensure that the oxide film is completely removed; Step 3, taking out the Kovar alloy sintered part of step 2, and removing the residual solution on the surface of the Kovar alloy sintered part; Step 4: Drying to remove the moisture on the surface of the Kovar alloy sintered part with residual solution on the surface.
2. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1, characterized in that: In the step 1, the components of the oxide film include FeO, Fe3O4, and Fe2O3; In the step 2, the mixed acid solution removes FeO, Fe3O4 and Fe2O3 in the oxide film.
3. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1, characterized in that: In the step 2, 1L of the mixed acid solution is prepared, and its components include: 90ml / L to 110ml / L of hydrochloric acid solution, 90ml / L to 110ml / L of nitric acid solution, 5g / L to 8g / L of thiourea, 2g / L to 5g / L of perchlorate, and the balance of deionized water.
4. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 3, characterized in that: The hydrochloric acid solution is prepared by mixing hydrogen chloride and water, and the specific gravity of hydrogen chloride to water in the hydrochloric acid is 1.19; The components of the nitric acid solution include nitric acid and water, and the specific gravity of nitric acid to water is 1.
42.
5. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 3, characterized in that: In the step 2, the process of preparing the mixed acid solution includes: (1) Measure 90ml~110ml of hydrochloric acid solution and pour it into a 1L beaker; (2) Measure 90 ml to 110 ml of nitric acid solution and slowly pour it into the hydrochloric acid solution while stirring. The liquid in the beaker is a mixed acid. (3) After the mixed acid is cooled to room temperature, deionized water is slowly added to the beaker until the liquid in the beaker is close to 1 L; (4) Weigh 5 g to 8 g of thiourea and 2 g to 5 g of permethrin, add them to the beaker, and stir them thoroughly to melt; (5) Slowly add deionized water to the beaker again until the liquid in the beaker is 1 L.
6. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1, characterized in that: In the step 2, during the process of removing the oxide film, the chemical reaction equation for completely removing the oxide film by the mixed acid solution includes: (1) The chemical reaction equation for removing FeO from the oxide film includes: FeO+2HCl=FeCl2+H2O, 3FeO+10HNO3=3Fe(NO3)3+NO↑+5H2O; (2) The chemical reaction equation for removing Fe3O4 from the oxide film includes: Fe3O4+8HCl=2FeCl3+FeCl2+4H2O, 3Fe3O4+28HNO3=9Fe(NO3)3+NO↑+14H2O; (3) The chemical reaction equation for removing Fe2O3 from the oxide film includes: Fe2O3+6HCl=2FeCl3+3H2O, Fe2O3+6HNO3=2Fe(NO3)3+3H2O.
7. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1, characterized in that: The step one comprises: Step (11) processing the Kovar alloy into a desired shape and size, and assembling and positioning the Kovar alloy and the glass through a mold; Step (12) The atmosphere in the electric furnace is air, and the heating temperature is 900° C. The Kovar alloy and the glass assembled in the mold are placed in the electric furnace, and the high-temperature surface of the Kovar alloy is oxidized to form an oxide film with a thickness of 200 nm to 800 nm. At the same time, the glass is melted by the heat, and the glass solidifies in the electric furnace and sintered with the surface of the Kovar alloy to form a Kovar alloy sintered part; In step (13), the Kovar alloy sintered piece is kept warm in the electric furnace until the glass is completely melted and then cooled. The cooled Kovar alloy sintered piece is immersed in the mixed acid solution in step 2.
8. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1, characterized in that: In the step 2, the Kovar alloy sintered piece is fixed with a hanger, and the operator wears protective gear and immerses the Kovar alloy sintered piece and the hanger into the mixed acid solution for a reaction time of 0.5 min to 2 min; specifically: The Kovar alloy sintered piece is fixed to the hanger, and the hanger is shaken to check whether the Kovar alloy sintered piece is firmly hung, and to ensure that the hanger and the Kovar alloy sintered piece will not fall off during the pickling process; During the preparation and pickling operations, workers must wear protective equipment to prevent the mixed acid solution from splashing and injuring workers.
9. The chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1 is characterized in that: In the step 2, before the Kovar alloy sintered piece is immersed in the mixed acid solution, the Kovar alloy sintered piece is first isolated and protected; specifically: The area of the Kovar alloy sintered part that does not need pickling is isolated and protected by a plastic sleeve, an adhesive tape or a tool.
10. A chemical method for effectively removing thick oxide film of Kovar alloy sintered parts according to claim 1, characterized in that: In the step 3, removing the residual solution on the surface of the Kovar alloy sintered part comprises: The Kovar alloy sintered part is rinsed with running cold water for 40 seconds to 60 seconds to remove the residual solution of the Kovar alloy sintered part; In the step 4, the drying treatment to remove the moisture on the surface of the Kovar alloy sintered part from the residual solution on the surface comprises: After the moisture on the surface of the Kovar alloy sintered piece is blown away by compressed air, the piece is placed in a blast drying oven and dried at 95±5° C. for 25 min to 40 min.
Citation Information
Patent Citations
Preparation method of Kovar alloy metallographic corrosive and corrosion method of Kovar alloy metallographic corrosive
CN116926548A